Bulbophylum sect. Cirhopetallum s. str. (Orchidaceae) in Vietnam with the description of a new species, B. thangii, and a new national record, B. fenestratum - Truong, Ba Vuong; Averyanov, Leonid V.; Maisak, Tatiana V.; Dang, Minh Quan; Nguyen, van Canh; Amlser, Roland; Nguyen, Quoc Bao; Dang, van Son (Phytotaxa, 2023)
The taxonomical survey of Bulbophyllum sect. Cirhopetallum s. str. with the key for identification of all four species occurring in Vietnam is presented. Bulbophylum thangii, belonging to this section and discovered in Khanh Hoa Province, southern Vietnam, is described as a new species for science. The new species shares prominent tooth on the inner side of stelidia with all species in its section but differs from them in warty or colliculate sepals and lip. Bulophyllum fenestratum from the same section is reported from Dong Nai Province as a new national record for the orchid flora of Vietnam. All species in the section are illustrated by plates with analytical color photos. Data on types, habitat, phenology, distribution, taxonomic remarks, and lists of studied specimens are reported for all species as well.